2021
DOI: 10.1116/6.0000964
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chemical bonding difference of ALD Mo on SiO2 and Al2O3 on the effective work function of the two gate stacks

Abstract: This study investigates molybdenum deposited by atomic layer deposition (ALD) as a potential gate metallization for flash memory devices. Polycrystalline (110)-oriented, with low-resistivity (∼16 μΩ cm) ALD Mo films were deposited on SiO2 and Al2O3 using hydrogen reduction of Mo-oxychloride precursor. On SiO2, an effective work function (EWF) of 4.75 ± 0.1 eV was obtained for as-deposited samples, and its value increased up to 4.9 ± 0.05 eV upon annealing at 600 °C, whereas on Al2O3, a stable EWF value of 5.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…It was expected that the deposition rate would be too low to grow a Mo thin film directly on the wafer, requiring a seed layer for initial nucleation. MoN thin films have been utilized as seed layers in previous studies as they have been demonstrated to be an antidiffusion barrier with excellent electrical and thermal stabilities, facilitating early nucleation [14,15]. Table 3 shows the deposition conditions of the MoN thin film deposited as a seed layer.…”
Section: Molybdenum-nitride (Mon) Seed Layer Process Conditionsmentioning
confidence: 99%
“…It was expected that the deposition rate would be too low to grow a Mo thin film directly on the wafer, requiring a seed layer for initial nucleation. MoN thin films have been utilized as seed layers in previous studies as they have been demonstrated to be an antidiffusion barrier with excellent electrical and thermal stabilities, facilitating early nucleation [14,15]. Table 3 shows the deposition conditions of the MoN thin film deposited as a seed layer.…”
Section: Molybdenum-nitride (Mon) Seed Layer Process Conditionsmentioning
confidence: 99%
“…Despite this, molybdenum metal thin films have been deposited by both CVD, [51][52][53][54][55][56][57] and ALD. [58][59][60][61][62] However, these examples all show the deposited metal to incorporate substantial impurities due to contamination from ancillary ligands or the reducing agent.…”
Section: Molybdenum Bis-imide Deposition Precursorsmentioning
confidence: 99%